The association between atrial fibrillation and Alzheimer's disease: fact or fallacy? A systematic review and meta-analysis. Issue 2 (February 2020) - Proietti, Riccardo; AlTurki, Ahmed; Vio, Riccardo; Licchelli, Luca; Rivezzi, Francesco; Marafi, Mariam; Russo, Vincenzo; Potpara, Tatjana S.; Kalman, Jonathan M.; de Villers-Sidani, Etiene; Bunch, T. Jared
Abstract : Background: The association between atrial fibrillation and dementia has been described. Whether a specific association exists between atrial fibrillation and Alzheimer's disease remains uncertain. This study aims to assess the association between atrial fibrillation and Alzheimer's disease through a systematic review and meta-analysis of the literature. Methods: An exhaustive search of electronic databases up to October 2018 was conducted. Studies that identified patients with and without atrial fibrillation as well as patients with and without Alzheimer's disease and reported results of at least one relevant outcome, including hazard ratio of the association between atrial fibrillation and Alzheimer's disease were included in this analysis. The hazard ratios and their confidence interval were then pooled using a DerSimonian and Laird random effects model. Results: Six studies enrolling a total of 56 370 patients were included. At baseline, the mean or median ages ranged from 50 to 78 years with a subsequent follow-up of 3 to 25 years. The random-effect pooled analysis showed a hazard ratio of 1.30 (95% confidence interval 1.01–1.59) and the heterogeneity was not significant, I 2 48.1%. All of the included studies were rated as good quality. Conclusion: Pooled analysis suggest that patients with atrial fibrillation may be exposed to an increased risk of developing new onset of Alzheimer's disease. Given the relevant clinical implications, further studies are required to corroborate these findings. Abstract : Supplemental Digital Content is available in the text